Question
upstudy study bank question image url

Solve the system of equations by the elimination method \( \left\{\begin{array}{l}4 x+y=5 \\ 8 x+3 y=12\end{array}\right. \) \( (x, y)=\square \)

Ask by Vargas Morrison. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( (x, y) = \left( \frac{3}{4}, 2 \right) \)

Solution

We are given the system:   4x + y = 5  (1)   8x + 3y = 12 (2) Step 1: Multiply equation (1) by -3 to set up cancellation for y.   -3(4x + y) = -3(5)   -12x - 3y = -15  (3) Step 2: Add equation (3) to equation (2):   (8x + 3y) + (-12x - 3y) = 12 + (-15)   (8x - 12x) + (3y - 3y) = -3   -4x = -3 Step 3: Solve for x:   x = (-3) / (-4) = 3/4 Step 4: Substitute x = 3/4 back into equation (1):   4(3/4) + y = 5   3 + y = 5   y = 5 - 3 = 2 Thus, the solution to the system is:   (x, y) = (3/4, 2)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the system of equations using the elimination method, we can start by manipulating the first equation. From \( 4x + y = 5 \), we can express \( y \) in terms of \( x \): \( y = 5 - 4x \). Now, we can substitute this expression for \( y \) into the second equation \( 8x + 3y = 12 \): \( 8x + 3(5 - 4x) = 12 \). Expanding this gives: \( 8x + 15 - 12x = 12 \). Combining like terms results in: \( -4x + 15 = 12 \). Subtracting 15 from both sides yields: \( -4x = -3 \). Dividing both sides by -4 gives us: \( x = \frac{3}{4} \). Now we can substitute \( x = \frac{3}{4} \) back into the expression for \( y \): \( y = 5 - 4\left(\frac{3}{4}\right) = 5 - 3 = 2 \). So the solution to the system of equations is \( (x, y) = \left(\frac{3}{4}, 2\right) \).

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy